Spectres of fascism : historical, theoretical, and international perspectives - Gandesha, Samir (Samir Suresh), 1965- (Pluto Press, 2020)
"Concerns over the rise of fascism have been preoccupied with the Trump presidency and the Brexit vote in the UK, yet, globally, we are witnessing a turn towards anti-democratic and illiberal forces. From the tragic denouement of the Egyptian Revolution to the consolidation of the so-called Gujarat Model in India under the leadership of Prime Minister Narendra Modi and the consolidation of the power of Turkish President Recep Tayyip Erdogan, to the recent election of Jair Bolsonaro in Brazil, fascist ideology, aesthetics, and personalities appear across the globe. Spectres of Fascism makes a significant contribution to the unfolding discussion on whether what we are witnessing today is best understood as a return to classic twentieth-century fascism or some species of what has been called "post-fascism." Applying a uniquely global perspective, it combines analyses of historical contexts, theoretical approaches, and contemporary geopolitics."--